Mantle xenoliths from the Veneto Volcanic Province, northern Italy: Sr-Nd-Pb and O isotope evidence for geochemical heterogeneity in the southalpine sub-continental lithosphere - GASPERINI D; BOSCH D; BRAGA R; BONDI M; MORTEN L.; MACERA, PATRIZIA (2004)
Abundant spinel-peridotite xenoliths occur in the Tertiary alkali basalts of the Veneto Volcanic Province (VVP, northern Italy). Whole rock major and trace elements, and Sr-Nd-Pb-O isotope data on a suite of xenoliths characterised by mg# [molar MgO/(MgO+FeO*)] > 88 have been performed. Whole rock major element variation defines a negative correlation trend between mg# and CaO, Al2O3, TiO2 and Na2O that indicates a variable depleted source. This trend is also supported by the compositional variations of spinels that are characterised by a strong Cr/(Cr+Al) ratio increase at a slight Mg/(Mg+Fe2+) ratio decrease. Furthermore, the xenoliths are variably enriched in LREE, K, Rb, Sr and P indicating metasomatic processes. The enriched xenoliths display significant positive Nb and Ta anomalies, incompatible element ratios, and Sr-Nd-Pb and O isotopic compositions similar to the host VVP alkaline basalts, which are characterised by a marked OIB-HIMU signature. Compared to various representative world-wide ultramafic xenoliths, the VVP xenoliths show geochemical similarities to those carried by alkaline basalts in tectonic settings dominated by the presence of hot spot magmatism (e.g. Canary and Kerguelen Islands, Massif Central, Eifel). Carbonatite-induced metasomatism does not appear to explain (e.g. unrelated LILE/HFSE ratios) the trace element enrichment in the VVP xenoliths. The depleted xenoliths are characterised by incompatible element patterns (e.g. troughs at Ba, Nb, and Ta) and ratios (e.g. high Rb/Nb, La/Nb, Th/Yb) likely related to a sedimentary (pelagic?) component in their source. Their Sr-Nd-Pb-O isotopic compositions fall within the field of MORB and altered oceanic crust. Similar features have been observed for ultramafic xenoliths collected in basalts from subduction-related environments (e.g. Marianas, Philippines, and Papua Nuova Guinea). In summary, the elemental and isotopic heterogeneities in the VVP xenoliths, which sample the subcontinental mantle of the Adria (i.e. paleo-Africa) plate, ...